Optimization of Chitosan Concentration in the Making of Edible Film From Corn (Zea Mays L.) - Pramesta, Deasycha Novelidia; Dewata, Indang (Universitas Negeri Padang, 2022)
Edible film is a thin plastic that has a thickness of less than 0.3 mm and is made from edible materials. This study aims to determine the effect of the concentration of chitosan in the manufacture of edible films, as well as to compare the physical and mechanical properties of edible films obtained with the standard values ​​set by the Japanese Industrial Standard (JIS) Z1707. In this study, variations in the concentration of chitosan were carried out to obtain a good edible film, with a concentration variation of 0%; 0.5%; 1%; 1.5%; and 2%. The obtained edible films were analyzed for thickness, tensile strength and elasticity (Young's modulus). Based on the research conducted, it was found that along with the addition of chitosan, the thickness, tensile strength and elasticity values ​​increased. Thickness values ​​range from 0.07 to 0.09 mm. The value of tensile strength and elasticity value obtained the optimum value at 1% chitosan concentration with a tensile strength value of 9,655 Mpa and an elasticity value of 12.41 Mpa. The thickness, tensile strength and elasticity values ​​obtained meet the standard values ​​set by the Japanese Industrial Standard (JIS).